Assessment of the development of strains/cracks in carbon-short-fiber-reinforced concrete (CSFRC) under static tensile loading using strain gauges and light-beam micrometer - Džolan, Ante; Fischer, Oliver; Jurišić, Marino (Građevinski materijali i konstrukcije, 2025)
Concrete is the most widely used material in the world today, but its extensive use also poses environmental risks due to high CO2 emissions. To mitigate these emissions, reducing concrete consumption in construction is crucial. Enhancing its mechanical properties, particularly low tensile strength, can accomplish this. Enhancing tensile strength allows for the construction of smaller cross-sections of concrete elements, resulting in more efficient material utilization. One effective method for strengthening concrete is through fiber reinforcement. In this study, short carbon fibers are used to reinforce the concrete, creating a material known as shortcarbon-fiber-reinforced concrete (CSFRC). The objective of this research is to advance the understanding of CSFRC's behavior under tensile stress. To do this, strain gauges and a light-beam micrometer (LBM) are used to track crack and strain growth, which gives information about how well the CSFRC is working overall.